(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Glass-fiber fabric composites are widely used in various applications. Its usage is largely determined by the bending behaviour of fabric composites in through-thickness direction. In this work we have selected three types of quasi three spacer fabric made of glass fibres to analyze their structure and conduct bending experiments. The surface morphology in up, back and side views, as well as weaving/knitting structure were also observed. It exhibited that there existed much static atmosphere within fabric composite for a high porous structure. Moreover, the three-points bending properties were also measured by Instron tester. The bending load and deflection curve of fabric composite were obtained. The Typical Bending Stress and Strain Curves were calculated and studied for biaxial spacer weft-knitted fabric (named as sample #1), tuck stitch spacer warp-knitted fabric (sample #2) and spacer woven fabric composite (sample #3). The testing results show that sample #1 had the highest indexes in bending stiffness, maximum bending stress and maximum bending load, followed by Samples #2 and #3. This can be attributed to the yarn's orientation in fabric composite, i.e., the yarn's crimp shape in thickness direction.